Asymptomatic primary biliary cholangitis in a young patient: an incidental finding - Kamarudin, Norhidayah; Chuan, Hun Ding; Md Isa, Nurismah; Md Pauzi, Suria Hayati; Abdul Wahab, Asrul (Ghazi University, 2020)
Primary biliary cholangitis (PBC) is an autoimmune disease that is increasingly recognized as an important cause of chronic liver disease. Incidental diagnoses are not uncommon. We report a case of a middle-aged female with persistently elevated ALP activity. During the investigation of cholestasis, anti-mitochondrial antibodies (AMA) were detected in her serum. Ductular reaction with cholestasis was observed in the liver biopsy sample. Based on these findings, a diagnosis of PBC was established and ursodeoxycholic acid therapy was commenced. After several weeks of treatment, biochemical improvement was noted.